Corruption, democracy and human rights - Chávez Filinich, Tatiana Myrlenko (2022)
Corruption constitutes a phenomenon that is rooted in different spaces and appears in multiple modalities. There is a close link between dictatorial and/or authoritarian regimes where a series of corrupt acts take place that directly violate human rights, in particular the full exercise of freedoms, life and personal security. However, corruption could also find space in democratic states, albeit weak or with precarious institutions. The rule of law, therefore, is often delegitimized and, even more so, the development of social rights and the implementation of policies that contribute to inclusion and effective and comprehensive citizenship, especially when it comes to vulnerable populations or where intersectionality is evident. State principles and obligations, as well as current regulations, efforts to make corruption visible and the creation of strategies and mechanisms that contribute to the fight against corruption are observed more clearly in the sentences issued by courts that are part of the protection of human rights at the level of the inter-American and European regions.